Clinical procedures used for the analysis of body composition. http://dx.doi.org/10.5007/1980-0037.2013v15n1p113 - Dartagnan Pinto Guedes (Universidade Federal de Santa Catarina, 2013)
According to the requirement for precision, accuracy and validation of information to be treated, clinical procedures can be characterized as an acceptable and accessible option for the analysis of components associated with body composition. The techniques with clinical features more commonly used are bioelectrical impedance and anthropometry by skinfold thickness. However, despite the greater feasibility in the face of laboratory procedures, clinical procedures have limitations and specifications regarding the use of their protocols, which should necessarily be considered when they are used. The purpose of this review is to provide a critical analysis about the use of bioelectrical impedance and anthropometry and explain the importance of carrying out well defined application standards to ensure more appropriate body composition estimation.